Preparation method and application of lithium ion battery negative plate

The production of lithium-ion battery negative electrode sheets through magnetron sputtering method and multiple coating technology solves the expansion problem of silicon-based materials during charging and discharging, and improves the gram capacity and cycle stability of the battery.

CN119495712APending Publication Date: 2025-02-21安徽得壹能源科技有限公司

Patent Information

Application Number
CN202411693404.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The silicon-based materials of existing lithium-ion batteries have expansion problems during charging and discharging, resulting in insufficient rate performance and poor cycle stability.

Method used

The negative electrode sheet of lithium-ion battery was prepared by magnetron sputtering method and multiple coating methods. By forming a stable silicon-based thin film and graphite active material layer, the gram capacity and charge and discharge efficiency of the negative electrode sheet were improved.

Benefits of technology

It effectively improves the capacity of the negative electrode of the battery, reduces the expansion of the silicon-based material, and improves the cycle stability and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151551100000091
    Figure BDA0005151551100000091
  • Figure HDA0005151551110000011
    Figure HDA0005151551110000011
Patent Text Reader

Abstract

The invention provides a preparation method and application of a lithium ion battery negative electrode plate, the lithium ion battery negative electrode plate comprises a negative electrode current collector, the surface of the negative electrode current collector comprises a first active material layer and a second coating layer, the first active material layer is prepared by a magnetron sputtering method, and the second coating layer is prepared by a magnetron sputtering method. The second coating layer is coated on the first active substance layer, the first active substance layer comprises a silicon-based thin film prepared by vacuum magnetron sputtering, and the second coating layer comprises a graphite active substance, a conductive agent, a dispersing agent and a binder. The internal aperture structure of the negative plate inhibits the expansion of the silicon-based material and improves the cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a method for preparing a negative electrode sheet of a lithium ion battery and its application. Background Art

[0002] Lithium ions have the advantages of high energy density, light weight, high voltage, and environmental protection, so they are widely used in mobile phones, digital cameras, UPS power supplies, electric vehicles and other equipment. At present, most commercial lithium-ion batteries use graphite negative electrodes. Although lithium-ion batteries using graphite negative electrodes have the advantages of high coulombic efficiency and good cycle performance, their theoretical capacity is very low, which limits the improvement of the specific capacity of the entire battery. The silicon negative electrode has a specific capacity that is ten times higher than that of the traditional carbon negative electrode (mass specific capacity: 4200mAh / g; volume specific capacity: 9786mAh / cm 3 ), and has a relatively low discharge potential (the average lithium de-lithiation potential is around 0.4V), and silicon is abundant in the earth's crust (its content in the earth's crust is second only to oxygen), is environmentally friendly, and has relatively stable chemical properties, and has been widely used in the semiconductor industry.

[0003] For example, Chinese patent application CN118299521A discloses a method for preparing a silicon-based lithium-ion negative electrode sheet that improves the rate performance of a battery cell. Active Si, conductive carbon black, single-walled carbon nanotubes, and modified carbon fibers are added to a mixture A to prepare a negative electrode slurry, which is then applied to the surface of a copper foil, and the negative electrode sheet is obtained after drying and rolling. The silicon-based lithium-ion negative electrode sheet of the invention participates in the preparation of a silicon-based lithium-ion battery negative electrode by introducing long-range conductive materials with high electronic conductivity such as VGCF, carbon fiber, and hollow carbon fiber, thereby improving the long-range conductivity of the silicon-based lithium-ion battery negative electrode sheet and improving the problem of insufficient rate performance caused by the expansion of silicon-based materials. However, the expansion problem of silicon-based materials during charging and discharging has not been fundamentally solved.

[0004] Chinese patent application CN201010243252.9 relates to a battery negative electrode and its preparation method. The invention solves the problem that the existing silicon-based materials used as battery negative electrodes undergo huge volume changes during Li insertion and extraction, which leads to the destruction of the internal structure of the material and affects the cycle performance of the electrode material. However, although the patent application solves some of the huge volume changes and cycle performance problems, there are still technical problems such as insufficient contact between the electrode material particles and insufficient rate performance of the battery cell. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a method for preparing a stable lithium-ion battery silicon-based material negative electrode sheet, which improves the gram capacity of the lithium-ion battery negative electrode material by magnetron sputtering and multiple coating methods, and reduces the expansion of the silicon-based material during the charging and discharging process. The method has at least one of the following advantages:

[0006] (1) It can effectively improve the battery negative electrode capacity and increase the battery energy density;

[0007] (2) Can effectively improve battery charging and discharging efficiency;

[0008] (3) Improve the internal pore structure of the negative electrode sheet, inhibit the expansion of silicon-based materials, and improve the cycle stability of the battery.

[0009] In one aspect of the present invention, the present invention provides a negative electrode sheet for a lithium-ion battery. According to an embodiment of the present invention, the negative electrode sheet for a lithium-ion battery includes a negative electrode current collector, the surface of the negative electrode current collector includes a first active material layer and a second coating layer, the first active material layer is prepared by magnetron sputtering, the second coating layer is coated on the first active material layer, the first active material layer includes a silicon-based film prepared by vacuum magnetron sputtering, and the second coating layer includes a graphite active material, a conductive agent, a dispersant, and a binder.

[0010] According to an embodiment of the present invention, the above-mentioned lithium-ion battery negative electrode sheet may further include at least one of the following additional technical features:

[0011] According to an embodiment of the present invention, the target material used in the magnetron sputtering method is a silicon target.

[0012] According to an embodiment of the present invention, the sputtering target material used for the vacuum magnetron sputtering is a silicon target with a purity of 99.99%, a size of 60 mm in diameter and a thickness of 5 mm, and is produced by China YUAN Technology Group Co., Ltd.

[0013] According to an embodiment of the present invention, the vacuum magnetron sputtering instrument used is a TRP-450 magnetron sputtering film deposition system produced by Shenyang Scientific Instrument Co., Ltd., Chinese Academy of Sciences.

[0014] According to an embodiment of the present invention, the second coating layer is made of the following components in percentage by mass: 95-98% graphite active material, 0.5-2.5% conductive carbon black, and 1.5-2.5% dispersant and binder.

[0015] According to an embodiment of the present invention, the dispersant and the binder are selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0016] According to an embodiment of the present invention, the content of the sodium carboxymethyl cellulose is 2.0%, and the content of the styrene-butadiene rubber is 0.5%.

[0017] In another aspect of the present invention, the present invention also provides a method for preparing a negative electrode sheet for a lithium-ion battery. According to an embodiment of the present invention, the method comprises:

[0018] S1: Cut the empty negative electrode current collector to the size of the sputtering area of ​​the vacuum chamber, and install the silicon target on the sputtering base;

[0019] S2: Start the high-frequency sputtering power supply and start pre-sputtering;

[0020] S3: after the pre-sputtering, sputtering the first active material layer begins to obtain a current collector containing the first active material layer;

[0021] S4: coating the second coating layer material on the first active material layer of the current collector containing the first active material layer to obtain the negative electrode sheet of the lithium ion battery.

[0022] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0023] According to an embodiment of the present invention, the second coating layer material comprises graphite active material, conductive agent, dispersant and binder. Part of the organic solvent is added to the second coating layer material during homogenization to adjust the viscosity.

[0024] According to an embodiment of the present invention, the second coating layer material is made of the following components in percentage by mass: 95-98% graphite active material, 0.5-2.5% conductive carbon black, and 1.5-2.5% dispersant and binder.

[0025] According to an embodiment of the present invention, the dispersant and the binder are selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0026] According to an embodiment of the present invention, the content of the sodium carboxymethyl cellulose is 2.0%, and the content of the styrene-butadiene rubber is 0.5%.

[0027] According to an embodiment of the present invention, the purity of the silicon target is 99.99%.

[0028] According to an embodiment of the present invention, the power of the power source for the pre-sputtering and the sputtering of the first active material layer is 30-60W, for example, 30W, 40W, 50W or 60W.

[0029] According to an embodiment of the present invention, the time for sputtering the first active material layer is 10-30 minutes, for example, 10 minutes, 20 minutes or 30 minutes.

[0030] According to an embodiment of the present invention, the pre-sputtering further includes: maintaining the vacuum chamber under vacuum pressure for 15-60 minutes, introducing high-purity argon gas, and repeating this process three times.

[0031] According to an embodiment of the present invention, the viscosity of the second coating layer material is 3000-6000 mPa.s.

[0032] According to an embodiment of the present invention, the negative electrode current collector is a copper foil or a composite current collector.

[0033] In another aspect of the present invention, the present invention also provides a method for preparing a negative electrode sheet of a lithium-ion battery. According to an embodiment of the present invention, the method comprises the following steps:

[0034] (1) Cut the empty negative electrode current collector (commonly copper foil, composite current collector) to the size of the sputtering area of ​​the vacuum chamber, install a silicon target on the sputtering base, the purity of the silicon target is generally 99.99%, and evacuate the chamber;

[0035] (2) After maintaining the vacuum pressure for 15-60 minutes, high-purity argon gas is introduced, and this process is repeated three times; the high-frequency sputtering power supply is started to start pre-sputtering;

[0036] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer;

[0037] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, and adjust the slurry dispersion to a viscosity of 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0038] (5) coating the negative electrode slurry obtained in step (4) on the surface of the current collector containing the first active material layer obtained in step (3), drying and rolling to obtain the negative electrode sheet of the lithium ion battery;

[0039] In another aspect of the present invention, the present invention further provides a negative electrode sheet for a lithium-ion battery. According to an embodiment of the present invention, the negative electrode sheet for a lithium-ion battery is prepared by the method described above.

[0040] In another aspect of the present invention, the present invention further provides a lithium ion battery. According to an embodiment of the present invention, the lithium ion battery comprises the above-mentioned negative electrode sheet of the lithium ion battery.

[0041] According to the embodiments of the present invention, the present invention has at least one of the following technical effects:

[0042] (1) The negative electrode sheet prepared according to the embodiment of the present invention has a high specific capacity;

[0043] (2) According to the embodiment of the present invention, the internal pore size of the negative electrode sheet is improved, and the DC internal resistance of the lithium-ion battery is reduced;

[0044] (3) The lithium battery obtained by the negative electrode sheet according to the embodiment of the present invention has high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0046] Figure 1 It is the capacity retention curve of the embodiment and the comparative example at 45°C. DETAILED DESCRIPTION

[0047] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0048] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0049] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0050] Embodiment 1:

[0051] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0052] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0053] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0054] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 40 W, and pre-sputtering began.

[0055] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 10 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition is completed;

[0056] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0057] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0058] Embodiment 2:

[0059] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0060] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0061] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0062] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 40 W, and pre-sputtering began.

[0063] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 20 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition is completed;

[0064] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0065] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0066] Embodiment 3:

[0067] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0068] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0069] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0070] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 40 W, and pre-sputtering began.

[0071] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 30 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition;

[0072] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0073] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0074] Embodiment 4:

[0075] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0076] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0077] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0078] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 60 W, and pre-sputtering began.

[0079] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 10 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition is completed;

[0080] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0081] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0082] Embodiment 5:

[0083] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0084] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0085] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0086] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 60 W, and pre-sputtering began.

[0087] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 20 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition is completed;

[0088] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0089] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0090] Embodiment 6:

[0091] The sputtering target used for the first active material layer is produced by China Research Institute Technology Group Co., Ltd.; the second active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0092] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0093] (1) Cut the empty negative electrode current collector into a size of 80*80 mm, install a silicon target with a purity of 99.99% on the high-frequency sputtering base, and evacuate the chamber to a vacuum degree of 10 -6 Pa;

[0094] (2) After maintaining the vacuum pressure for 30 minutes, high-purity argon gas was introduced, and this process was repeated three times. The high-frequency sputtering power supply was started, the power supply was set to 60 W, and pre-sputtering began.

[0095] (3) After the light emitted by the pre-sputtering target material stabilizes, turn on the rotary switch of the sputtering area, and then open the protective cover of the sputtering area; start sputtering the first active material layer. After sputtering deposition for 30 minutes, turn off the power supply, stop sputtering, and take out the current collector after sputtering deposition;

[0096] (4) Add the second active material layer slurry into the stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain the negative electrode slurry for standby use;

[0097] (5) The negative electrode slurry obtained in step (4) is applied to the surface of the current collector on which the first active material layer is deposited obtained in step (3), and the coating surface density is 12 mg / cm 2, drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0098] Comparative Example 1:

[0099] The active material layer formula is made of the following components in mass percentage: Shanshan (industry trademark) 96.5% graphite active material, 1.0% conductive carbon black, 2.0% sodium carboxymethyl cellulose, and 0.5% styrene-butadiene rubber.

[0100] The above-mentioned lithium-ion battery negative electrode sheet is prepared by the following method:

[0101] (1) Cut the empty negative electrode current collector into a size of 80*100mm.

[0102] (2) Add the second active material layer slurry into a stirrer according to the formula ratio, homogenize and disperse, and adjust the viscosity to 3000-6000 mPa.s to obtain a negative electrode slurry for standby use;

[0103] (3) The negative electrode slurry obtained in step (2) is applied to the surface of the empty current collector cut in step (1) with a coating surface density of 12 mg / cm 2 , drying and roller pressing (compacted density is 1.55 g / cm3) to obtain the negative electrode sheet of the lithium ion battery;

[0104] The negative electrode sheets of the lithium-ion batteries of the above embodiment and the comparative example were assembled into finished batteries according to the same process, and their capacity, efficiency, AC impedance and DC internal resistance were tested respectively.

[0105] Table 1 shows the design parameters of the pole pieces of the embodiment and the comparative example;

[0106] Table 2 shows the first discharge capacity and efficiency of the embodiment and the comparative example at room temperature 25°C and 0.5C. It can be seen that the capacity and efficiency of the battery in the embodiment are significantly higher than those in the comparative example.

[0107] Table 3 is a comparison of the DC internal resistance of the embodiment and the comparative example when charged for 30 seconds at room temperature 25°C and 3C different SOCs. The impedance of the embodiment is lower than that of the comparative example, which is beneficial to reduce the polarization of the battery and improve the cycle stability performance;

[0108] Attached Figure 1 It is a capacity retention curve diagram of the embodiment and the comparative example at 45°C and 1C charge and 1C discharge. The cycle attenuation trend of the embodiment is better than that of the comparative example, indicating that the negative electrode sheet prepared by the embodiment can improve the cycle.

[0109] Table 1. Information parameters of the electrode pieces of the embodiments and comparative examples

[0110] Whether the active substance is stratified Sputtering power / W Sputtering time / min Example 1 yes 40 10 Example 2 yes 40 20 Example 3 yes 40 30 Example 4 yes 60 10 Example 5 yes 60 20 Example 6 yes 60 30 Comparative Example 1 no / /

[0111] Table 2. Gram capacity and initial charge and discharge efficiency of examples and comparative examples at room temperature

[0112] Negative electrode capacity (mAh / g) First charge and discharge efficiency Example 1 361.3 89.7% Example 2 377.6 87.5% Example 3 390.8 85.2% Example 4 378.2 88.2% Example 5 395.4 84.1% Example 6 420.8 83.8% Comparative Example 1 342.7 91.2%

[0113] Table 3. Charging impedance of the examples and comparative examples at 25°C

[0114]

[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A negative electrode sheet for a lithium-ion battery, characterized in that: The negative electrode sheet of the lithium-ion battery includes a negative electrode collector, the surface of the negative electrode collector includes a first active material layer and a second coating layer, the first active material layer is prepared by magnetron sputtering, the second coating layer is coated on the first active material layer, the first active material layer includes a silicon-based film prepared by vacuum magnetron sputtering, and the second coating layer includes a graphite active material, a conductive agent, a dispersant and a binder.

2. The negative electrode sheet of a lithium-ion battery according to claim 1, characterized in that: The target material used in the magnetron sputtering method is a silicon target; Optionally, the second coating layer is made of the following components in percentage by mass: 95-98% graphite active material, 0.5-2.5% conductive carbon black, and 1.5-2.5% dispersant and binder; Optionally, the dispersant and binder are selected from sodium carboxymethyl cellulose and styrene-butadiene rubber; Optionally, the content of the sodium carboxymethyl cellulose is 2.0%, and the content of the styrene-butadiene rubber is 0.5%.

3. A method for preparing a negative electrode sheet for a lithium ion battery, characterized in that: S1: Cut the empty negative electrode current collector to the size of the sputtering area of ​​the vacuum chamber, and install the silicon target on the sputtering base; S2: Start the high-frequency sputtering power supply and start pre-sputtering; S3: after the pre-sputtering, sputtering the first active material layer begins to obtain a current collector containing the first active material layer; S4: coating the second coating layer material on the first active material layer of the current collector containing the first active material layer to obtain the negative electrode sheet of the lithium ion battery.

4. The method according to claim 3, characterized in that The second coating layer material includes graphite active material, conductive agent, dispersant and binder; Optionally, the second coating layer material is made of the following components in percentage by mass: 95-98% graphite active material, 0.5-2.5% conductive carbon black, 1.5-2.5% dispersant and binder; Optionally, the dispersant and binder are selected from sodium carboxymethyl cellulose and styrene-butadiene rubber; Optionally, the content of the sodium carboxymethyl cellulose is 2.0%, and the content of the styrene-butadiene rubber is 0.5%.

5. The method according to claim 3, characterized in that: The purity of the silicon target is 99.99%; Optionally, the power of the power supply for the pre-sputtering and sputtering of the first active material layer is 30-60W; Optionally, the sputtering time of the first active material layer is 10-30 minutes.

6. The method according to claim 3, characterized in that The pre-sputtering further includes: maintaining the vacuum chamber under vacuum pressure for 15-60 minutes, introducing high-purity argon gas, and repeating this for 3 times.

7. The method according to claim 3, characterized in that The viscosity of the second coating layer material is 3000-6000 mPa.s.

8. The method according to claim 3, characterized in that The negative electrode current collector is copper foil or a composite current collector.

9. A negative electrode sheet for a lithium-ion battery, characterized in that: The lithium-ion battery negative electrode sheet is prepared by the method according to any one of claims 3 to 8.

10. A lithium ion battery, characterized in that: Including the ion battery negative electrode sheet as described in claim 1, 2 or 9.

Citation Information

Patent Citations

  • Porous silicon-based cathode for lithium battery and preparation method thereof

    CN101894940A

  • Preparation method of silicon-based lithium ion negative electrode plate for improving rate capability of battery cell and lithium ion battery

    CN118299521A

Cited By

  • Multilayer silicon / graphite composite electrode material, layer-by-layer assembly method and application

    CN121282167A